Fertility differences between two wild-type Drosophila melanogaster lines correlate with differences in the expression of the Jheh gene, which codes for an enzyme degrading juvenile hormone - O. V. Andreenkova; N. V. Adonyeva; V. M. Efimov; N. E. Gruntenko (Вавиловский журнал генетики и селекции)
Juvenile hormone plays a “status quo” role in Drosophila melanogaster larvae, preventing the untimely metamorphosis, and performs a gonadotropic function in imagoes, ensuring the ovaries’ preparedness for vitellogenesis. The decreased level of juvenile hormone results in reproductive disorders in D. melanogaster females including a delay in the oviposition onset and a fertility decrease. Another factor that can affect the insect reproduction is an infection with the maternally inherited symbiotic α-proteobacterium Wolbachia. The present study is devoted to the analysis of the expression of two juvenile hormone metabolism genes encoding enzymes of its synthesis and degradation, juvenile hormone acid O-methyltransferase ( jhamt) and juvenile hormone epoxide hydrase (Jheh1), respectively, in four wild-type D. melanogaster lines, two of them being infected with Wolbachia. Lines w153 and Bi90 were both derived from an individual wild-caught females infected with Wolbachia, while lines w153T and Bi90T were derived from them by tetracycline treatment and are free of infection. Line Bi90 is known to be infected with the Wolbachia strain wMel, and line w153, with the Wolbachia strain wMelPlus belonging to the wMelCS genotype. It was found that infection with either Wolbachia strain does not affect the expression of the studied genes. At the same time, it was shown that the w153 and w153T lines differ from the Bi90 and Bi90T lines by an increased level of the Jheh1 gene expression and do not differ in the jhamt gene expression level.  Analysis of the fertility of these four lines showed that it does not depend on Wolbachia infection either, but differs between lines with different nuclear genotypes: in w153 and w153T, it is significantly lower than in lines Bi90 and Bi90T. The data obtained allow us to reasonably propose that the inter-line D. melanogaster polymorphism in the metabolism of the juvenile hormone is determined by its degradation (not by its synthesis) and correlates with the fertility level.